DETERMINANTS OF STOCK RETURN ON AGRICULTURAL COMPANY - INTAN, AFRODINDA; STELLA, STELLA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this research is to test and to analyze empirically the effect of current ratio, debt to equity ratio, return on assets, earnings per share, and price to earnings ratio on the stock return. The population of this research is the companies of agriculture sectors, that are listed on the Indonesia Stock Exchange. Using purposive sampling method, with 15 companies as the sample of this research and also representing each of the mining sub-sector during 2014-2020 period. The data analysis technique used is the Multiple Linear Regression Analysis and Panel Data Approach. The result of this research showed that the Current Ratio (CR), Debt to Equity Ratio (DER), Retun on Asset (ROA), Earnings per share (EPS), and Price to earnings ratio (PER) have no influence on stock returns.